1999
DOI: 10.1136/bjsm.33.3.204
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements and electrolytes in human resting mixed saliva after exercise.

Abstract: Objectives-Exercise is known to cause changes in the concentration of salivary components such as amylase, Na, and Cl. The aim of this investigation was to evaluate the eVect of physical exercise on the levels of trace elements and electrolytes in whole (mixed) saliva. Methods-Forty subjects performed a maximal exercise test on a cycle ergometer. Samples of saliva were obtained before and immediately after the exercise test. Sample concentrations of Fe, Mg, Sc, Cr, Mn, Co, Cu, Zn, Se, Sr, Ag, Sb, Cs, and Hg we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 24 publications
3
40
1
Order By: Relevance
“…Other studies found higher concentrations. Chicharro et al reported 10 times the average concentration of Cu, 100 times the concentration of Zn, and over 200 times the concentration of Fe and Mn as our findings [37]. Wang et al reported Zn at 1,180 ± 214 ng/mL, Cu at 822 ± 159 ng/mL, but also Mn at 2.7 ± 1.5 ng/mL [4].…”
Section: Discussionsupporting
confidence: 76%
“…Other studies found higher concentrations. Chicharro et al reported 10 times the average concentration of Cu, 100 times the concentration of Zn, and over 200 times the concentration of Fe and Mn as our findings [37]. Wang et al reported Zn at 1,180 ± 214 ng/mL, Cu at 822 ± 159 ng/mL, but also Mn at 2.7 ± 1.5 ng/mL [4].…”
Section: Discussionsupporting
confidence: 76%
“…This ability may be physiologically relevant in the oral environment. Chicharro et al measured concentrations of both Mn and Fe in the saliva of 40 young men (10). Variability was high, but mean concentrations of 80 to 84 M for Fe and 25 to 36 M for Mn were reported.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to exercise stress and antioxidant status, one study has shown that a decrease in levels of Mn superoxide dismutase after nutritional intervention with a yeast cell preparation that is rich in antioxidants and trace elements and minerals can be interpreted as a sign of reduced free radical stress (20). In this context, it is notable that after intense physical exercise, Mn levels in saliva decreased (24). Metalloenzymes (other than superoxide dismutase) for which Mn is a cofactor include arginase, pyruvate carboxylase and glutamine synthetase (25).…”
Section: Discussionmentioning
confidence: 99%